An Analysis of Politeness Strategies Used by Teacher and Students in English Class at SMPN 1 Mojo Kediri - Mukharomah, Lailatul; Sumanto, Ossa Bodhi Tala (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Politeness is a vital component in communication as it assists in preventing misunderstandings, reducing conflict, and building harmony between interlocutors, such as communication between the educator and learners in the educational setting. This descriptive qualitative study attempts to explore the types and preferred politeness techniques employed by both educators and learners in an English class. An English teacher and 40 students of class 7 G SMPN 1 Mojo Kediri were the participants of this research. The research's primary instrument was an observation by video recording and documentation, which was afterward examined by the researchers through data reduction, display of data, conclusion drawing, and triangular validation. The data was evaluated employing Leech's politeness theory, involving the following maxims: tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The findings revealed that the instructor employed all six maxims, namely tact, generosity, approbation, modesty, agreement, and sympathy maxim. While the students only employed four maxims, they displayed tact, modesty, agreement, and sympathy maxim. There are 132 utterances between the instructor and students, and it was discovered that the agreement maxim was the most frequently employed politeness approach by the teacher and students, with 41 frequencies used by the teacher and 37 frequencies used by the students.